A point-wise least squares spectral analysis (LSSA) of the Caspian Sea level fluctuations, using Topex/Poseidon and Jason-1 observations - Sharifi, M.; Forootan, E.; Nikkhoo, M.; Awange, Joseph; Najafi-Alamdari, M. (Pergamon, 2013)
The Caspian Sea has displayed considerable fluctuations in its water level during the past century. Knowledge of such fluctuation is vital for understanding the local hydrological cycles, climate of the region, and construction activities within the sea and along its shorelines. This study established a point-wise satellite altimetry approach to monitor the fluctuations of the Caspian Sea using a complete dataset of TOPEX/Poseidon for the period 1993 to the middle of 2002, and its follow-on Jason-1 for the period 2002 to August 2009. Therefore, 280 virtual time-series were constructed to monitor the fluctuations. The least squares spectral analysis (LSSA) method is, then employed to find the most significant frequencies of the time-series, while the statistical method of principle component analysis (PCA) is applied to extract the dominant variability of level variations. The study also used the observations of TOPEX/Poseidon and Jason-1 over the Volga River along with 5 years of Volga’s water discharge to study its influence on the Caspian Sea level changes.The LSSA results indicate that the lunar semidiurnal (M2) and the Sun semidiurnal (S2) frequencies are the main tidal frequencies of the Caspian Sea with the mean amplitude of 4.2 and 2.8 cm, respectively. A statistically significant long-term frequency (12.5-years period) is also found from altimetry and tide gauge observations. A phase lag, related to the inter-annual frequencies of the Volga River was detected from the point-wise time-series showing level propagation from the northwest to the southeast of the sea. The cross-correlation between the power spectrum of Volga and that of the northern-most, middle, and southern-most points within the Caspian Sea were respectively 0.63, 0.51 and 0.4 of zero-lag correlation, corroborating the influence of the Volga River. The result of PCA also shows that different parts of the Caspian Sea exhibit different amplitudes of level variations, indicating that the point-wise approach, when employing all available satellite measurements could be a suitable method for a preliminary monitoring of this inland water resource as it gives accurate local fluctuations.